APLIKASI KOMPOS Trichoazolla PADA TANAH GAMBUT DAN ULTISOL TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI MAIN NURSERY - Setiawan, Heri; Armaini, Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The aim of this research is to know combination of medium and Trichoazolla compost dosage which can increase the growth of oil palm seedlings in main nursery and determine the best combination of Trichoazolla compost dosage and medium for growth of oil palm seedlings in main nursery. This research uses Completely Randomized Design (RAL) consisting of two factors, the first factor is planting medium consisting of three medium peat level, ultisol medium and mixed peat and ultisol (1: 1). The second factor was Trichoazolla compost consisting of Trichoazolla compost dose 0 g / plant, 75 g / plant, 100 g / plant, 125 g / plant, 150 g / plant. Of the two factors, we got 15 treatment combinations with 3 replications. The parameters measured were the height increase of seedlings, the increase of the number of leaves, the increase of seedling diameter, root canopy ratios, dry weight of seedlings, palm seed oil quality index. The results showed that the growth of oil palm seedlings on peat, ultisol and mixed peat moss with ultisol composted with Trichoazolla 75 g / plant-150 g / plant, was better than without Trichoazolla compost and was able to achieve the standard of seed quality, while Mixed medium composted Trichoazolla compound nutrient seed quality index. Composting of Trichoazolla in peat, ultisol and peat and ultisol combinations may increase seedling height, increase in number of leaves, increase in diameter of tubers in oil palm seedlings.Keyword : Trichoazolla, land and ultisol, oil palm, main nursery